THE CORRELATION AMONG PARENTS’ EDUCATION, INCOME, MOTIVATION AND ENGLISH LEARNING ACHIEVEMENT OF THE STATE JUNIOR HIGH SCHOOL 27 OF PALEMBANG - PURWANTO BAMBANG (Universitas Jambi, 2017)
Some problems occur in process of learning English, such as, limitation of vocabulary, the difficultness of understanding grammar, uninterested of students in English lesson, less practicing to improve speaking ability in expressing something, difficult to understand meaning and concept of passage, and hard to express something in writing context. Based on the problems, the researcher wants to investigate the Correlation among Parents Education, Income, Motivation and English Learning Achievement. Furthermore, the populations of the research is the ninth students of SMPN 27 of Palembang consisting 341 students, from the population, 100 students were represented as the sample which taken through probability sampling technique. The instrument to collect the data used questionnaires for parents’ education, income, motivation and English learning achievement was taken by students’ final score in Rapot. While to analyze the data, it was used multiple correlation in SPSS 20 for Windows. The data analysis showed that Ryx1x2x3 = 0.685 at the significant level 0.05. ), with R2 = 0.469 (or 46.9% = 47%) contributed of Parents’ Education, Income, Motivation and 53% from other factors. and for the criteria of significant test was Fcount = 28.220 > Ftable(98) = 0.195.. The result of hypothesis that showed that there is significant correlation among Parents Education, Income, Motivation and English Learning Achievement. Therefore, it is suggested that parents can give big influence for students achievement especially for achievement in learning English where parents’ part can control students progress and development in learning.